2013
DOI: 10.1098/rstb.2012.0477
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the long view of ecological change in tundra systems

Abstract: Despite uncertainties related to sustained funding, ideological rivalries and the turnover of research personnel, long-term studies and studies espousing a long-term perspective in ecology have a history of contributing landmark insights into fundamental topics, such as population- and community dynamics, species interactions and ecosystem function. They also have the potential to reveal surprises related to unforeseen events and non-stationary dynamics that unfold over the course of ongoing observation and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…There is only fragmented and scarce data (in time and space) on sea ice extent prior to the generation of spatially explicit sea ice extent information by satellite observations in the late 1970s [ Post and Høye , ]. Since Iceland's settlement in circa 870 A.D., records were kept of sea ice incidence by Icelandic fisheries [ Polyak et al ., ], enabling the development of a sea ice index for the period A.D. 1600–1850 [ Ogilvie and Jónsdóttir , ].…”
Section: Sea Ice Observation and Reconstructionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is only fragmented and scarce data (in time and space) on sea ice extent prior to the generation of spatially explicit sea ice extent information by satellite observations in the late 1970s [ Post and Høye , ]. Since Iceland's settlement in circa 870 A.D., records were kept of sea ice incidence by Icelandic fisheries [ Polyak et al ., ], enabling the development of a sea ice index for the period A.D. 1600–1850 [ Ogilvie and Jónsdóttir , ].…”
Section: Sea Ice Observation and Reconstructionsmentioning
confidence: 99%
“…This has contributed to the decrease in ice age, with a drop from 4+ years old ice constituting 33% of the total ice extent in the mid‐1980s to 3.1% in 2016 [ Tschudi et al ., ]. The continuing decline in sea ice cover is expected to have a diverse range of consequences including a warmer, wetter Arctic, impacts on terrestrial and marine productivity, changes to global atmospheric and ocean circulation patterns, terrestrial fauna and flora population fragmentation and habitat reduction, increased marine species interaction and connectivity, and northward expansion of lower latitude species [ Overland and Wang , ; Screen and Simmonds , ; Francis and Vavrus , ; Post and Høye , ; Overland et al ., ; Bintanja and Andry , ; Vavrus et al ., ]. The knowledge of the dynamics behind such changes is constantly evolving, and the importance of factors such as the Arctic Oscillation—AO; defined as the principal component of Northern Hemisphere sea level pressure and regarded as the most influential mode of atmospheric circulation and climate in the Arctic [ Thompson and Wallace , ; Comiso and Hall , ]—and associated changes in ocean current and sea ice dynamics remains under active research [e.g., Rigor et al ., ; Comiso and Hall , ; Barnes and Screen , ; Ding et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter issue is particularly challenging in arctic datasets because there is some evidence that communities in extreme environments tend to be less dynamic and to exhibit very slow succession rates [ 36 , 37 ]. The use of long-term datasets, which are rare for arctic ecosystems [ 38 ], could aid in resolving these issues [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…While continuous, long‐term records of phenology are relatively common in temperate ecosystems, very few such records exist for Arctic regions (Post & Høye, ). Short‐term monitoring of phenological responses to experimental warming has demonstrated that Arctic plants flower earlier when warmed (Arft et al ., ; Hollister & Webber, ; Hollister et al ., ), but these short‐term responses have been shown to overestimate responses to long‐term experimental warming and underestimate responses to ambient warming (Chapin et al ., ; Hollister et al ., ; Wolkovich et al ., ; Kremers et al ., ).…”
Section: Introductionmentioning
confidence: 99%